FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY PADA PERUSAHAAN CONSUMER CYCLICAL - Soleha, Wiranda Warda; Yantiana, Nella; IKhsan, Syarbini (Journal of Information System, Applied, Management, Accounting and Research, 2024)
The timeliness of the company in reporting its audited financial statements greatly affects the quality of a company's financial statements. The audit process plays an important role in ensuring the accuracy of financial statements to be an important source of information for investors, creditors, governments, and other parties in making decisions. This study aims to determine the effect of company size, audit opinion, and company age on audit delay in consumer cyclical companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023. The samples used in the study can be obtained from the Indonesia Stock Exchange (IDX) website in the form of financial statements. The data analysis techniques used in this study are descriptive statistics, multiple linear regression analysis, and hypothesis testing. Based on the results of the study shows that the size of the company has a significant effect on audit delay, as well as audit opinions. However, the age of the company has no effect on the audit delay. Simultaneously, the variables used in this study, namely company size, audit opinion, and company age, have an influence of 15% expressed with an R square value.